PEMBUATAN BAHAN DAN PELATIHAN IDENTIFIKASI FORMALIN SERTA BORAKS DALAM MAKANAN DENGAN METODE SEDERHANA BAGI SEKELOMPOK MASYARAKAT YANG BERASAL DARI BEBERAPA KABUPATEN DI PAPUA - Ilham Salim; Frans P. Kafiar (JURNAL PENGABDIAN PAPUA, 2019)
The use of formalin and borax as food preservatives is prohibited by the government, because this material is toxic (poison).However, some survey results indicate that several types of food ingredients in traditional markets and other food traders still contain formalin and borax. Therefore, it is necessary to introduce to the general public  how to identify formalin and borax use simple materials and tools. Qualitative test of formalin content in food was used fehling A and fehling B solution. While the qualitative test of borax content was used in turmeric which was prepared in the form of tumeric paper. Activities between speakers and trainees were held face-to-face and the practice of identifying food ingredients containing both formalin and borax were carried out directly in the laboratory. From the results of the activities that had been carried out, it can be concluded that although the ingredients for identification of formalin and borax in food ingredients obtained from simple ingredients, cheap and easy to obtain such as fehling A and fehling B and turmeric in the form of tumeric paper, but they can identify food ingredients contains formalin and borax. Fehling A and Fehling B solutions can identify qualitatively with significant results between that contain  and  not  contain formalin. Similarly, tumeric paper can identify qualitatively with significant results between that contain and not contain borax in food ingredients. Participants were very motivated to apply the results of this activity to the community where they live especially after seeing the results of qualitative tests using fish purchased at the Hamadi traditional market during this service. Qualitative test results using fehling A and B solutions identified red snapper purchased at the traditional Hamadi market using preservatives from formalin.Keywords: Formalin, Borax, Preservatives, Fehling A, Fehling B, Turmeric